2011
DOI: 10.1186/1475-925x-10-88
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of compensatory processes of postnatal hypoxia in newborn piglets applying short-term nonlinear dynamics analysis

Abstract: BackgroundNewborn mammals suffering from moderate hypoxia during or after birth are able to compensate a transitory lack of oxygen by adapting their vital functions. Exposure to hypoxia leads to an increase in the sympathetic tone causing cardio-respiratory response, peripheral vasoconstriction and vasodilatation in privileged organs like the heart and brain. However, there is only limited information available about the time and intensity changes of the underlying complex processes controlled by the autonomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Due to higher respiratory frequencies (>0.6 Hz), which only occur at very young ages, the direction is less pronounced or even abolished. In an animal study on newborn piglets significant differences for cardiorespiratory coupling was revealed by indices from JSD due to hypoxia following reoxygenation (Reulecke et al, 2011 ; Schulz et al, 2011 ). Hypoxia initially led to greater HR complexity and to stronger cardiovascular and respiratory coupling, maintaining life in the newborn piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Due to higher respiratory frequencies (>0.6 Hz), which only occur at very young ages, the direction is less pronounced or even abolished. In an animal study on newborn piglets significant differences for cardiorespiratory coupling was revealed by indices from JSD due to hypoxia following reoxygenation (Reulecke et al, 2011 ; Schulz et al, 2011 ). Hypoxia initially led to greater HR complexity and to stronger cardiovascular and respiratory coupling, maintaining life in the newborn piglets.…”
Section: Discussionmentioning
confidence: 99%
“…By means of stationary NN interval time segments, a possible bias on our final results will be excluded or at least minimized. In accordance with Schulz et al (Schulz et al, 2011 ), we therefore extracted and used only 30 min NN time segments for daytime and nighttime hours, thereby fulfilling the pre-selection criterion for most stationary segments.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure reliable HRV measurements from these four-hour BBI sleep phases, only 20-minute periods during nocturnal non-rapid eye movement sleep that met the pre-selection criterion for most stationary segments were automatically extracted and visually after-checked by means of a stationary detection algorithm (Matlab). The algorithm for extracting stationary segments can be found in [26].…”
Section: Plos Onementioning
confidence: 99%